CORRELATION OF THE NURSE’S COMMUNICATION WITH THE PATIENT’S SATISFACTION (In the Mawar Room, RSUD Jombang, Jombang district) - Tiara Hana Frinsiska (Jurnal Keperawatan, 2013)
In the globalization era, the hospital servise become a hard competition among the private andthe government hospital even domestically and internasionally or globally. More over the patientoften fells unsatisfied with the quality and the information they got from the medical expert, it is could berelatedwith the low communication between the medical expert with patien. One thing which isinfluenced it can be seen from the nurse’s ability on terapeutic communicate, because thiscommunication is also influential to the satisfaction level. This research was held to analyzedthe nurse’s communication with the patient’s satisfaction in the Mawar room of RSUD Jombang.Kind of this research was analytic research, the research method was cross sectional. Thepopulation numbers were 32 persons, while the sample numbers as 30 persons who taken bysimple random sampling technique. Data was collected used questionnaire. The dependent variable wasthe nurse’s communication and the independent variable was the patient’s satisfaction. Dataprocessed used editing,coding, scoring and tabulating with spearman rank statistic test.Based on the research got that half of the respondents such as 11 persons (37%) of the nursemade good communication and most of the patient’s satisfaction level. Most of half of nurse’scommunication was in good with the patient’s satisfaction on the level of satisfied as 10 persons(33%). The result of spearman rank statistic tes got the value of ρ= 0,045 < α= 0,05.The conclussion of the research was there were relation between the nurse’s communication withthe patient’s satisfaction in the Mawar room of RSUD Jombang.Key words: Communication, satisfaction, patient, nurse.